2014
DOI: 10.1111/jnc.12639
|View full text |Cite
|
Sign up to set email alerts
|

LPS or ethanol triggers clathrin‐ and rafts/caveolae‐dependent endocytosis of TLR4 in cortical astrocytes

Abstract: Toll-like receptor 4 (TLR4) activation and signalling in glial cells play critical roles in neurological disorders and in alcoholinduced brain damage. TLR4 endocytosis upon lipopolysaccharide (LPS) stimulation regulates which signalling pathway is activated, the MyD88-dependent or the TIR-domain-containing adapter-inducing interferon-b (TRIF)-dependent pathway. However, it remains elusive whether ethanol-induced TLR4 signalling is associated with receptor internalization and trafficking, and which endocytic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 57 publications
2
57
0
2
Order By: Relevance
“…In contrast, Lee et al reported that stimulation of astrocytes with LPS led to the induction of IFN-β through activation of NF-κB (Lee et al, 2005). A recent study also showed that IFN-β mRNA level was significantly increased 3 h after LPS treatment in astrocytes (Pascual-Lucas et al, 2014). In addition, LPS was found to induce IFN-β through p38 MAPK and NF-κB pathways in U373MG human astrocytoma cells (Imaizumi et al, 2013).…”
Section: Discussionmentioning
confidence: 85%
“…In contrast, Lee et al reported that stimulation of astrocytes with LPS led to the induction of IFN-β through activation of NF-κB (Lee et al, 2005). A recent study also showed that IFN-β mRNA level was significantly increased 3 h after LPS treatment in astrocytes (Pascual-Lucas et al, 2014). In addition, LPS was found to induce IFN-β through p38 MAPK and NF-κB pathways in U373MG human astrocytoma cells (Imaizumi et al, 2013).…”
Section: Discussionmentioning
confidence: 85%
“…Cholesterol content varies across brain regions, and thus alcohol may regulate a broad range of cell-surface receptor-induced signalling in a brain region-specific manner by changing the structure, fluidity and composition of membrane lipids, including cholesterol-enriched rafts. Several studies have started to address this possibility in cells 184, 185 and in vivo 30, 186, 187 . However, data from animal models of alcohol consumption are sparse 30 , in part owing to technical limitations.…”
Section: Conclusion and Open Questionsmentioning
confidence: 99%
“…2.1). Ethanol and LPS can promote TLR4 endocytosis through clathrin- and caveolae-dependent pathways, and in cortical astrocytes, TRIF-dependent signaling relies on the clathrin pathway, while disruption of rafts/caveolae inhibits both the MyD88- and TRIF-dependent signaling pathways (Pascual-Lucas, Fernandez-Lizarbe, Montesinos, & Guerri, 2014). …”
Section: Immune Regulation Of Ethanol Consumption and Ethanol Regumentioning
confidence: 99%